Price Flexibility, Credit Availability, and Economic Fluctuations: Evidence from the United States, 1894-1909 - Calomiris, Charles W.; Hubbard, R. Glenn (Quarterly Journal of Economics, 1989)
The importance of disturbances in financial markets for real economic activity and the positive association between price level and output movements typically are explained by appeal to a combination of nominal aggregate demand shocks (particularly money-supply shocks) and rigid prices. We argue that this view is inconsistent with evidence for short-run responsiveness of prices and gold flows to nominal disturbances during the pre-World War I gold-standard era. We offer an alternative explanation that connects financial markets and real activity through disturbances to the availability of credit. This approach links comovements in prices and output through real effects in credit markets associated with price-level shocks. Empirical analysis, using monthly data for the pre-World War I period, supports the assumption of rapid price adjustment, and the credit-supply interpretation of the transmission of financial shocks. Disturbances to credit availability, including price shocks, contribute substantially to our empirical explanation of output fluctuations during this period.